Performing Sexuality in a Digital Environment: GenZee Culture, Technology and the Politics of Morality in Northern Nigeria - ADINOYI, Oyiza Rhoda (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
In a highly morally and religiously charged Northern Nigeria, how is the appropriation and performativity of sexuality negotiated and contested between older generations and the Gen Zees through digital technologies? The growing influence of social media platforms presents an unregulated public avenue for Gen Zee Nigerians to digitally express and perform their sexuality against cultural values. However, this digitally sponsored visibility has resulted in a near-crisis of nudity that conflicts with the region’s conservative and often guarded religious norms on bodily exposure, modesty, and moral decency. Using both primary and secondary historical sources, this study argues that social media platforms have created an intergenerational gulf that pitches the older generation against the Gen Zees’ unbridled public sexual self-expressions. This conflict has led to the state deployment of censorship, backlash, police arrest, and even physical violence on the Gen Zees. Through a qualitative analysis of selected cases of arrest and humiliations of Gen Zees, this paper finds that the tensions between inherent cultural value and the technologically-geared quest for self-expression and identity of the Gen Zees in Northern Nigeria stoke embers of irreconcilable intergenerational differences in conservative Islamic Northern Nigeria in a democratic state. Felix Guattari and Gilles Deleuze framework of assemblage is used alongside interviews and digital ethnography of selected case studies which are explored in the paper. This research aims to contribute to the understanding of youth, modernity, and technology in Africa as regards the performativity of sexuality.